2021
DOI: 10.21037/gs-21-177
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of risk factors for lymph node posterior to the right recurrent laryngeal nerve metastasis in papillary thyroid carcinoma

Abstract: Background: Whether the lymph node posterior to the right recurrent laryngeal nerve (LN-prRLN) should be dissected is still controversial. This meta-analysis aimed to assess the risk factors for LN-prRLN metastasis in papillary thyroid carcinoma (PTC). Methods:We retrieved relevant studies published before May 2020 from the Wanfang Data, CNKI, PubMed, Embase, Web of Science and Cochrane Library databases. Heterogeneity was assessed with the Q-test and inconsistency index and sensitivity analysis and subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…This study did not find a significant association between gender, age, tumor size, uni-multifocality, prelaryngeal lymph nodes metastasis, left CLN metastasis, and LN-prRLN metastasis. However, a significant association was reported by previous studies on PTC (14)(15)(16)(17). Using univariate and multivariate analyses, we confirmed that ETE, lateral lymph node metastasis, the number of metastatic LN-arRLN were independent predictors of LN-prRLN metastasis, which was consistent with previous reports (6,14,15,18).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study did not find a significant association between gender, age, tumor size, uni-multifocality, prelaryngeal lymph nodes metastasis, left CLN metastasis, and LN-prRLN metastasis. However, a significant association was reported by previous studies on PTC (14)(15)(16)(17). Using univariate and multivariate analyses, we confirmed that ETE, lateral lymph node metastasis, the number of metastatic LN-arRLN were independent predictors of LN-prRLN metastasis, which was consistent with previous reports (6,14,15,18).…”
Section: Discussionsupporting
confidence: 92%
“…However, a significant association was reported by previous studies on PTC (14)(15)(16)(17). Using univariate and multivariate analyses, we confirmed that ETE, lateral lymph node metastasis, the number of metastatic LN-arRLN were independent predictors of LN-prRLN metastasis, which was consistent with previous reports (6,14,15,18).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, Area VI B dissection is necessary for patients with right-sided thyroid cancer. In a meta-analysis, Zhou et al ( 27 ) found that patients younger than or equal to 45 years old were more likely to develop Area VI B metastasis, and the number of lymph node metastasis in this region was related to the impaired survival of young patients ( 28 ). In our study, the average age of patients was not more than 35 years old.…”
Section: Discussionmentioning
confidence: 99%